Nonlinear backstepping control of a partially shaded photovoltaic storage system - Sabri Khadija; El Maguiri Ouadia; Farchi Abdelmajid (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Many power converter architectures and control approaches, both traditional and unconventional, have been developed, investigated, and adjusted to handle the challenge of tracking the maximum power points of a partially shaded photovoltaic (PV) system, which fluctuates with meteorological conditions (radiation and temperature). A DC-DC converter was used as the power conditioning unit to determine the system’s maximum efficiency. In this research, we focus on developing a nonlinear controller for a DC-DC converter to track the overall maximum power point in a PV storage system under partial shading situations. This study presents a combination of two MPP search algorithms with a backstepping controller. The particle swarm optimization (PSO) and variable step Perturb and Observe (P&O)with global scan (VSP&O/GS) algorithms supply the PV output reference voltage to the backstepping controller in order to recover the maximum power from photovoltaic (PV) systems. The simulation results of the methods compared to the proposed maximum power point (MPPT) algorithm are simulated and examined in the MATLAB/Simulink environment under non-uniform irradiation conditions. To demonstrate the performance and limits of each approach in tracking the maximum power point.